The Way, Nursing Care Quality, Affects the Patients Healing - Ghulam Mustafa Rajput, Musarat Fatima, Bharat Lai, Pir Bux Jokhio (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: Identification of factors that affect the care of patient by nursing perspective and its all-round consequences on the healing ofpatient. Methods: This observational study was conducted at Begum Bilqees Sultana Institute of Nursing, Peoples University of Medical & Health Sciences ( PUMHS ), Shahecd Benazir Abad from June 2016 to December, 2016. Five (05 ) point Likert’s scale was developed to measure the responses of various categories of nurses about the knowledge they possess concerning the healing ofpatient. Results: Withstanding the result of this study, it is found that the sub-standard quality care may hamper the healing ofpatient. Conclusion: Nurse patient ratio, quality of nursing education, and the managerial characteristics are among the factors, that may affect the healing of patient. .